Pallitative care in rural and remote areas. Challenges facing rural nurses in palliative cancer care in the far North of Norway - Edvardsen, Trine Lise; Lorem, Geir F; Mehus, Grete (Nordisk sygeplejeforskning, 2020)
In Finnmark, the northernmost county of Norway, many villages are remote and scattered between vast stretches of uninhabited land, with mountain crossings that are often closed in winter or where one can only drive in single file behind a snowplough. This may mean periodic total isolation and daily challenges with long distances to other professionals and hospitals. These special circumstances mean that nurses must act more independently than elsewhere. Objectives: The aim was to explore the challenges of rural nurses in palliative cancer care, and the prerequisites to maintain a suitable professional standard in their nursing. Methods: This study is qualitative with an explorative design and reports the results of the content analysis of interviews with five nurses, living in small, multi-ethnic villages. Findings: The main finding of the study is that the nurses experienced themselves as being alone geographically and professionally in their practice of palliative care. The established infrastructure for performing advanced nursing in patients’ homes is poorly adapted to the geographical and professional situation in rural areas such as Finnmark, and suboptimal information about patients arriving from hospitals can compromise the quality of care. Advanced nursing is performed when specialists are far away and there is no palliative team, and they care for patients who are often their family members, friends and acquaintances, which involves role ambiguity and a risk of over-involvement. Conclusion: The study shows that requirements to enhance palliative cancer care are to establish palliative teams, discharge summaries present in transition, the necessary drugs and medical equipment for several days, and relevant training of personnel.